Enhancing the drug addiction treatment service by introducing a new residential treatment model in the Philippines: A qualitative study - Shogo Kanamori; Tomohiro Shirasaka; Ma. Teresa Iñigo; Alfonso Villaroman; Rosalina Noguera-Caoile; Aya Mizusawa; Jasmin Peralta; Takayuki Harada (BMC, 2024)
Abstract Background There is an increased demand for quality treatment and rehabilitation services for people who use drugs (PWUDs) in the Philippines. In response, the Philippines Government's Department of Health (DOH) has established a new residential treatment model, Intensive Treatment and Rehabilitation Program for Residential Treatment and Rehabilitation Centers (INTREPRET), and integrated it into the existing treatment service platform of 21 DOH-owned Treatment and Rehabilitation Centers (TRCs). We conducted a qualitative study to identify the changes engendered by the implementation of this treatment model. Methods Data were collected through individual face-to-face interviews. We interviewed purposefully selected 29 patients and 35 facilitators of INTREPRET group sessions in seven TRCs. We transcribed the interview records and organized the narrative information into key themes using thematic analysis during the coding process. Results The changes perceived by the study participants included the attitude and behavior of patients, attitude and competency of facilitators, relationship between facilitators and patients, treatment planning and review process, efficient and standardized treatment services, and monitoring mechanisms of the patient's recovery process. Participants also noted challenges in INTREPRET implementation, including family participation in therapy sessions, lack of facilitators, securing a conducive place for conducting sessions, and reproducing workbooks. Conclusions The results imply that the introduction of INTREPRET could improve treatment service quality and the effectiveness of treatment, which were primarily associated with behavioral changes in patients, improved relationship between patients and facilitators, and INTREPRET's alignment with key international treatment standards. However, despite the positive changes perceived by the participants, certain challenges pertaining to family participation in therapy sessions and the lack of resources were identified. These criticisms must be addressed by DOH, along with an integration of INTREPRET into its policy and strategic framework, to ensure the effectiveness and sustainability of the new treatment model.